BIOGRAFI SOEMARDHI THAHER SEBAGAI TOKOH PENDIDIKAN RIAU - FAHMI, YUSNI FAHMI; isjoni, Prof. Dr. Isjoni, M.Si; BUNARI, Bunari, S.Pd M.Si (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
SOEMARDHI THAHER BIOGRAPHY AS A RIAU EDUCATION FIGURE Yusni Fahmi *, Prof. Dr. Isjoni, M.Sc **, Bunari, S.Pd M.Sc ***E-mail: Yusnifahmi23@gmail.com, Isjoni@yahoo.com, Bunari@lecturer.unri.ac.idCp: 082386866597 Historical Education Study ProgramDepartment of Social Sciences EducationFaculty of Teacher Training and EducationRiau University Abstract: Soemardhi Thaher is an educational figure who has a lot of role in advancing education in Riau. The purpose of this study is to find out the educational history of Soemardhi Thaher, to find out the efforts made by Soemardhi Thaher in advancing education, and to find out the obstacles experienced by Soemardhi Thaher in advancing education. The method used in this study is qualitative. Data obtained from interview results are then analyzed in their own language. The research location is Pekanbaru City. This research began to be implemented from the beginning of the title of this research was submitted until this thesis was completed. Data collection techniques used are interview techniques, library study techniques, documentation techniques, and data analysis techniques. The results showed that Soemardhi Thaher had a role in advancing education in Riau, namely by making various efforts in advancing education in Riau. Key Words: Biography